Photoredox catalytic radical fluorosulfonylation of olefins enabled by a bench-stable redox-active fluorosulfonyl radical precursor - Peng Wang; Honghai Zhang; Xingliang Nie; Tianxiao Xu; Saihu Liao (Nature Communications, 2022)
Sulfonyl fluorides are compounds with potential application in chemical biology and drug discovery, but their preparation can be challenging. Here, the authors present a type of bench-stable fluorosulfonyl radical reagents that enable radical fluorosulfonylation reactions via photoredox catalysis.